Literatur Review Determinan Preeklamsia pada Primigravida - Siti Choirul Dwi Astuti (JIDAN (Jurnal Ilmiah Bidan), 2022)
Background: Preeclampsia is a syndrome unique to human pregnancy and is often associated with increased maternal and fetal complications. Preeclampsia is also the second leading cause of maternal death and the leading cause of maternal death in many parts of the world. The increase in preeclampsia experienced an increase in first child pregnancies an average of 2.4% among all pregnancies. Objective: To analyze the determinants of preeclampsia in primigravida based on the existing literature. Methods: Literature searches were conducted on scientific sites such as ScienceDirect, Pubmed, Elsevier, NCBI, DOAJ, Proquest, Microsoft Academic, Sage Journal, Oxford Academic, LIPI, ResearchGate, JSTOR and Scrib.id using the keywords preeclampsia and primigravida. Results: The search results found 156 articles but only 9 articles were used and described the determinants of preeclampsia in primigravida and other articles that were eliminated were not used because they did not describe the determinants of preeclampsia in primigravida. Conclusion: The determinants of preeclampsia in primigravida include maternal age, lead levels, alcohol use, miscarriage, calcium consumption, body mass index, systolic blood pressure and cigarette use.